Economic Geography - Key Concepts - Sarah Box (New Zealand Government, The Treasury, 2000)
Economic geography can help us understand why people and firms choose to locate where they do, whether these are good choices from a broader efficiency/resource allocation viewpoint, and what the implications of these choices are for the distribution of income and wealth. This paper is an attempt to synthesise the key pieces of recent literature on economic geography and think about how the concepts may apply to New Zealand. The paper first builds a framework of the key forces affecting the geographic location of people and firms. The framework splits the concepts into exogenous and endogenous forces, with a particular focus on agglomerating and dispersing forces. The framework can be used to think about location decisions both within countries and between countries, and a closer look is taken at how the concepts apply to New Zealand at the international level. The paper then explores whether location decisions can be a problem from efficiency or equity perspectives and looks at possible roles for intervention. The paper highlights that location decisions are influenced by many factors and that density can offer many benefits to people and firms. Fundamental questions are raised about whether New Zealand as a whole can maintain a critical mass of activity. There are also important questions about how we might deal with poor or declining regions.
Keywords: 330